PROFESSIONAL INTERPRETERS’ NOTE-TAKING IN CONSECUTIVE INTERPRETING = Tốc ký của phiên dịch viên chuyên nghiệp trong dịch kế tiếp - Dương, Thị Thu Hương (2020)
Note-taking has proved itself to be important in consecutive interpreting training. However, this skill presents serious challenges for interpreting students which explained clearly in empirical researches. Therefore, to offer suggestions for students to solve their problems, the study sought to investigate strategies of professional interpreting through analyzing their notes and audio in consecutive interpreting. Analysis of data, previously collected and classified, indicated that each interpreter used different note-taking strategies which depended on his background knowledge, his memory capacity and interpreting conditions. Based on practical interpreting experience, note-taking was regarded as a supporting technique to help consecutive interpreters retrieve part of information of the source text and relieve strains on the memory. To fulfill this function, notes of interpreters should be as clear and brief as possible. It was important to emphasize that notetaking was not governed by any single rules. It was highly personal. Moreover, interviews with professional interpreters provided valuable advice for students to improve their note-taking skills. The study was expected to support individuals who were interested in this topic and interpreting student at the University of Languages and International Studies in their interpreting training. For further study, it would be better if note-taking is examined together with other related skills and techniques in a larger scale of subjects.